Start a revolution : stop acting like a library - Bizzle, Ben; Flora, Maria (ALA Editions, an imprint of the American Library Association, 2015)
Bizzle shows how successful libraries introduce new ideas into their presentations, web presence, and digital services. Marketing campaigns can be a challenge, and Bizzle shares universal concepts to promote a successful social media presence and increase community awareness of your library.--